Consumer environment stimulation: Are consumers aware of manipulation? - Perwangsa Nuralam, Inggang (Faculty of Economics and Business, University of Muhammadiyah Malang, 2023)
This study examines consumer behavior responding to environmental stimuli in original and manipulated online environments. This study aims to modify, alter, or affect independent variables in an experimental study design to gain new insights. The independent variable examined in this study is e-servicescape. We involved 85 participants worldwide to respond to the e-servicescape on the Spotify music platform. The e-servicescape environment stimuli consist of ambient factors, spatial layout and functionality, signs, symbols, artifacts, financial security, and interactivity. The quasi-experiment was implemented and found that consumers exhibit different behaviors and respond better to a pleasant environment rather than a manipulated one. The findings of this study are an early indication for companies to present a pleasant environment for consumers in a service environment.